(3OjhGf eGLO GdHMQGfjs - (3eGLO Hf gGTe Hf Ydj Hf eQJVj Hf Ydj Hf eGLO GdMSjfj,J (B1022 (3g` s ((3eMeO GdSeGhj s)
(3ChdgG (B:s
(3bGd QMeg Gddg jQKj LOg GdMSjf Ydjg GdSdGe(B: (3Hcj hdjS Ydj UHQ HeYPhQ ef bO CWd Ydjg YTQ YGThQ s
(3BNQgG (B:s
(3aCUHMrJ JQhb GdaDGO cCfeG SbJfj YbGQkG BNQ Gddjd UQNO s
(3GfXQg eY eLehYI TYQjI aj Bd GdHjJs
(3JGQjN haGI GdeDda aj GdCYdGe (B1028(3g```s
(3ofHPI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B120s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B189 s
Keywords: (3GdCOHs